2006
DOI: 10.1111/j.1468-2982.2005.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Life and Activity Limitations in Migraine Patients after Prophylaxis. A Prospective Longitudinal Multicentre Study

Abstract: Improved health-related quality of life (HRQOL) and reduced activity limitations are prime objectives of migraine therapy, but no data on the effect of preventive treatments on these outcomes are available. We monitored changes in HRQOL using the Short Form 36 (SF-36) and headache-related activity limitations using the Migraine Disability Assessment Score (MIDAS) in 141 consecutive migraine without aura patients on prophylaxis. A total of 102 patients completed the 3-month study. Mean (SD) number of headache d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 28 publications
2
63
0
3
Order By: Relevance
“…Of increasing importance is the impact of clinical measures on patient-perceived quality of life, performance in daily activities (work and familial-social duties). For examples see (136)(137)(138)(139)(140).…”
Section: Statisticsmentioning
confidence: 99%
“…Of increasing importance is the impact of clinical measures on patient-perceived quality of life, performance in daily activities (work and familial-social duties). For examples see (136)(137)(138)(139)(140).…”
Section: Statisticsmentioning
confidence: 99%
“…Using the SF-36 Health Survey 6 to examine quality of life, studies showed highly statistically significant changes across the range of scores with as little as 6 months of treatment. 7,8 With a migraine-specific quality-of-life assessment, broad improvements of at least moderate size and an effect that persisted over a prolonged period of observation were found across domains. 9 …”
Section: Impact Of Preventive Treatmentmentioning
confidence: 99%
“…The drugs for migraine prophylaxis are not completely effective or safe (3). The use of complementary preventive treatments has been growing worldwide that can be decrease the frequency and severity of migraine attacks with minimal side effects (5,6).…”
Section: Introductionmentioning
confidence: 99%